Transcriptomic analysis reveals ethylene as stimulator and auxin as regulator of adventitious root formation in petunia cuttings - Druege, Uwe; Franken, Philipp; Lischewski, Sandra; Ahkami, Amir H.; Zerche, Siegfried; Hause, Bettina; Hajirezaei, Mohammad R. (Frontiers in Plant Science, 2014)
Adventitious root (AR) formation in the stem base of cuttings is the basis for propagation of many plant species and petunia is used as model to study this developmental process. Following AR formation from 2 to 192 hours after excision (hpe) of cuttings, transcriptome analysis by microarray revealed a change of the character of the rooting zone from stem base to root identity. The greatest shift in the number of differentially expressed genes was observed between 24 and 72 hpe, when the categories storage, mineral nutrient acquisition, anti-oxidative and secondary metabolism, and biotic stimuli showed a notable high number of induced genes. Analyses of phytohormone-related genes disclosed multifaceted changes of the auxin transport system, auxin conjugation and the auxin signal perception machinery indicating a reduction in auxin sensitivity and phase-specific responses of particular auxin-regulated genes. Genes involved in ethylene biosynthesis and action showed a more uniform pattern as a high number of respective genes were generally induced during the whole process of AR formation. The important role of ethylene for stimulating AR formation was demonstrated by the application of inhibitors of ethylene biosynthesis and perception as well as of the precursor aminocyclopropane-1-carboxylic acid, all changing the number and length of AR. A model is proposed showing the putative role of polar auxin transport and resulting auxin accumulation in initiation of subsequent changes in auxin homeostasis and signal perception with a particular role of Aux/IAA expression. These changes might in turn guide the entrance into the different phases of AR formation. Ethylene biosynthesis, which is stimulated by wounding and does probably also respond to other stresses and auxin, acts as important stimulator of AR formation probably via the expression of ethylene responsive transcription factor genes, whereas the timing of different phases seems to be controlled by auxin.